Assessment of Cerebral Vasomotor Reactivity in Patients With Primary Open-angle Glaucoma and Ocular Hypertension Using the Breath-Holding Index. Issue 2 (February 2021) - Arslan, Gurcan D.; Olgun, Ali; Ozcan, Delil; Gökcal, Elif; Guven, Dilek; Asil, Talip
Abstract : Précis: Patients with ocular hypertension (OHT) do not show impaired cerebral vasodilation responses to hypercapnia but patients with primary open-angle glaucoma (POAG) do. Impaired vasoreactivity in patients with POAG may have neuronal or vascular origins and increase stroke risk. Purpose: To investigate changes in cerebral blood flow and cerebral vasomotor reactivity using the breath-holding index in patients with POAG and OHT, to examine whether these parameters contribute to the risk of ischemic stroke. Methods: Thirty patients with POAG, 30 patients with OHT, and 30 age- and sex-matched healthy control subjects were included in this university hospital-based, cross-sectional, and observational study. Eyes with a greater degree of visual field loss and/or more severe optic disc damage were selected for the study in patients with POAG, whereas in patients with OHT and controls, the study eye was chosen randomly. The mean blood flow velocity and breath-holding index were measured in the middle cerebral artery ipsilaterally in patient and control groups, by using transcranial Doppler ultrasonography. Results: The mean blood flow velocity and breath-holding indexes were significantly lower in patients with POAG than in the control group (all P <0.05). In the OHT group, the mean blood flow velocity and breath-holding indexes were not different from those in the control group. Conclusions: Patients with POAG have impaired vasodilation response to hypercapnia. Presumably, the neuronal changes and deterioration of the endothelium-mediated vasodilatation in patients with glaucoma may disrupt the regulation of arteries and potentially present functional insufficiency on vasoreactivity. Moreover, impaired cerebral vascular regulation may contribute to the increased risk of stroke in patients with POAG.